Defense mechanism as a response to trauma in “Take a Break” from Arash Buana Logic Mess album - Rizky, Sylvia; Farida, Hana (Pioneer: Journal of Language and Literature, 2025)
This research explores the expression of psychological trauma in “Take a Break”, one of the songs in the debut album by Indonesian singer-songwriter Arash Buana, Logic Mess (2022). The song presents a personal narrative shaped by emotional distress, inner conflict, traumatic experiences, and the journey to deal with them. Using Sigmund Freudian view on defense mechanisms, this study discuses how trauma is portrayed and processed throughout the song lyrics. The methodology used in this research is a qualitative descriptive analysis. The finding shows that the trauma experienced by the song character is resolved through various defense mechanisms such as denial, sublimation, rationalization, regression, and displacement which also confirms the relevance of Freud’s theory in interpreting the inner dynamics of an individual.